Revealing Mathematics Learning Difficulties Among Students with Numerical Dyscalculia: An Analysis of Conceptual Understanding in Mathematics - Najwa Olifia Annnisa Rambe; Kamid Kamid; Rohati Rohati (Journal of General Education and Humanities, 2025)
This study employs qualitative descriptive case studies to examine mathematics learning difficulties in class VII students with dyscalculia, focusing on the use of mathematical concepts. Dyscalculia can be interpreted as a learning difficulty in calculating, although calculating skills are an essential foundation for solving mathematical problems and a primary means of mastering other fields of study. This study aims to analyse how students with dyscalculia experience difficulties in using mathematical concepts. This attitude focuses on three indicators of learning difficulties: (1) difficulty understanding concepts, (2) difficulties in calculations, and (3) difficulty in solving problems. This study was conducted at SMP Negeri 6 Jambi City, Jambi, Indonesia, in April 2025. Technical data collection, including written tests and interviews. This discovery indicates that students struggle to understand and apply mathematical concepts in algebraic operations. The observed errors include difficulties in conducting calculation operations, errors in writing positive and negative signs, and final answers that do not address the problem. In addition, according to the interview results, students acknowledge difficulties in completing additional operations, such as subtraction and multiplication, and have limited knowledge of algebraic concepts, including variables, coefficients, and constants. The findings offer a concrete illustration of these difficulties, particularly in algebraic operations.